Value Enhancement of PT Indosat - Natalina, Melda; Soekarno, Subiakto (The Indonesian Journal of Business Administration, 2014)
Abstract- PT IndosatTbk is one of the biggest three telecommunication provider in Indonesia. For the last five years, Indosat has a decreasing performance from its earning profit, revenue growth and share price that tend to decrease. In order to know the cause of decreasing profit is by analyzing its external and internal environment. External analysis is using PEST analysis or Political, Economic, Social and technology and five porter analysis to know its industry analysis. While internal analysis is used to know company performance from its revenue, expenses and profit earning. Besides, financial ratio analysis is used to compare its performance with competitor. Dupont analysis is used to analyze profit earning from Return on Asset and Return on Equity. Return on asset of Indosat in 2013 isÂ  -0.05103 while ROE is -0.1684 due to negative earning profit. Eventhough Indosat still make profit, but from its economic profit the result is no economic value. The cause of decreasing profit is due to revenue growth is lower than other competitor also increasing expenses that cannot covered by its revenue. From internal and external analysis, telecommunication industry has a several player and number of subscriber from the biggest three company, Telkomsel, XL and Indosat are higher than number of Indonesia population. Proposed solution is how to increase its revenueÂ  especially from data service that currently has an increasing demand and how to make cost efficiency. Solution is to increase its technology in order to serve costumer demand in data sector. The result can be seen from targeted stock price that would increase into Rp 7599,-Keywords: Financial Ratio, EVA, Discounted cash flow, Valuation